Determination of the Calcium Sulfate Hemihydrate Content by Regression Analysis Using the Initial Setting Time - Bing Li (Archives of Civil Engineering, 2020)
In this paper, we randomly select 75 sets data of calcium sulfate hemihydrate (CSH) content and initial setting time, and the traditional test method of CSH and analyses initial setting time was used by complexometric titration. So the close relationship between them was studied in depth, which classification fitting data to be analyzed by regression analysis. The result shows that this regression analysis method can accurately determine CSH content in modified industrial by-product gypsum. The determination method has the advantages of simplification and rapid operation. As well as, the XRF quantitative analytical method was used to test the CSH content, which verified the accuracy of regression analysis method. The results also show that this method has high accuracy, and can simplify the traditional experimental process. The method developed is easier and more convenient and has broad prospects in application.